Software-defined laser ultrasonics: Non-destructive testing - Hass, Klaus (2019)
In this work we propose and implement the use of software defined optical interferometry for the development of laser ultrasound non-destructive testing. The interferometer is conceived as an optoelectronic system that can be controlled by software. The system itself consists of five interconnected blocks: An optical system (a heterodyne interferometer), an Electrical-Optical block (a laser + an acousto-optic modulator), an Optical-Electrical block (a balanced photodetector), a software defined hardware (a software defined radio platform), and a programmable controller (a personal computer). In particular, the selected software defined hardware includes a field programmable radio frequency transceiver. On the one hand, it can synthesize the stimulus signals for the acousto-optic modulator which splits the reference and test beams. On the other hand, it can process the photo-detected high-frequency signals accordingly. This software defined radio platform not only simplifies the experimental scheme but also has such a high sensibility that provides a wide dynamic range. In order to show the performance of the system for non-destructive testing, we analyze the signals produced on aluminium plates to detect flaws in weld seams.